Metallurgical Processing of CoCrFeNi High-Entropy Alloy - P. Müller; A. Zadera; L. Čamek; M. Myška; V. Pernica (Archives of Foundry Engineering, 2024)
High-entropy alloys (HEA) is a group of metallic materials that is currently experiencing great development in materials science. While conventional alloys are based on a majority of a primary element with some number of added elements, HEAs are based on multiple (usually conventional alloys are based on a majority of a primary element with some number of added elements, HEAs are based on multiple (usually more than 5) elements that reach equimolar/equiatomic content. With the right combination of elements, properties can be achieved that could predispose HEAs for practical applications. In the fabrication of HEAs in previous research, pure metals have been predominantly used as the charging material. However, the use of common industrial charge with limited purity is crucial for the more economically viable use of HEAs in industry. Such a charge material may contain accompanying elements which may have an undesirable effect on the properties of the alloy. In order to achieve optimum alloy properties, it is necessary to minimise their content using various metallurgical processes The aim of the work was the metallurgical processing of CoCrFeNi alloy melted from scrap metal in an induction furnace. The desired reduction of carbon (to 100 ppm) and nitrogen content (from 660 to ~60 ppm) was reached by using carbon reaction under vacuum. Significant reduction in oxygen content (to ~120 ppm) was reached after a deoxidation with aluminium and slight reduction in sulphur content (~25%, to 120 ppm) was reached after a desulphurisation with rare earth metals.